Characterization of the avian GLUT1 glucose transporter: differential regulation of GLUT1 and GLUT3 in chicken embryo fibroblasts. - Wagstaff, P (1995)
Vertebrate cells that are transformed by oncogenes such as v-src or are stimulated by mitogens have increased rates of glucose uptake. In rodent cells, the mechanisms whereby glucose transport is up-regulated are well understood. Stimulation of glucose transport involves an elevation in mRNA encoding the GLUT1 glucose transporter that is controlled at the levels of both transcription and mRNA stability. Cloning and sequencing of chicken GLUT1 cDNA showed that it shares 95% amino acid sequence similarity to mammalian GLUT1s. Nevertheless, unlike mammalian GLUT1 mRNA, it was not induced by v-src, serum addition, or treatment with the tumor promoter 12-O-tetradecanoylphorbol 13-acetate in chicken embryo fibroblasts. Rather, the induction of glucose transport in chicken embryo fibroblasts by v-src, serum, and 12-O-tetradecanoylphorbol 13-acetate was associated with induction of GLUT3 mRNA level and GLUT3 transcription. Rat fibroblasts were also found to express both GLUT1 and GLUT3 isoforms, but v-src induced GLUT1 and not GLUT3. This suggests that animal cells require both a basal and an upregulatable glucose transporter and that these functions have been subsumed by different GLUT isoforms in avian and mammalian cells.